Platelet factor 4 binds to interleukin 8 receptors and activates neutrophils when its N terminus is modified with Glu-Leu-Arg. - Clark-Lewis, I (1993)
Amino acid deletion and mutagenesis experiments have indicated that the sequences Glu-Leu-Arg (ELR) preceding the first cysteine at the N terminus of interleukin 8 (IL-8) is required for receptor binding and neutrophil activation. Platelet factor 4 (PF4) is structurally related to IL-8 (35% sequence identity) but lacks the N-terminal ELR sequence and comparable effects on neutrophils. We introduced the ELR sequence at the N terminus of PF4 and found that the modified protein was a potent neutrophil activator and attractant. On the other hand, when the ELR sequence was introduced into the corresponding positions of two other proteins related to IL-8, gamma-interferon-inducible protein IP10 and monocyte chemoattractant protein 1, neither of them acquired neutrophil-activating properties, indicating that besides ELR additional structural determinants of IL-8 and PF4 are important for binding to IL-8 receptors. The conservation of these binding determinants suggests that PF4 may have evolved from a neutrophil activating protein.